541 Cognitive Hyperarousal, Sleep Problems and Temperament Linked to Impaired Maternal-Infant Bonding. (3rd May 2021) - Arnett, Lily; Kalmbach, David; O'Brien, Louise; Pitts, D'Angela; Harb, Nicholas; Drake, Christopher
Abstract: Introduction: Emerging evidence links maternal and infant sleep problems to impairments in the mother-to-infant bond, but the independence and directionality of these associations remain unclear. The present study characterized concurrent and prospective effects of maternal sleep disturbances and poor infant sleep on the mother-infant relationship. As common sequalae of problematic sleep, nocturnal cognitive hyperarousal and daytime sleepiness were investigated as facilitating mechanisms. Methods: Sociodemographic information and clinical symptoms were measured prenatally then weekly across the first two postpartum months in 67 women. Participants reported insomnia symptoms, sleep duration, snoring, daytime sleepiness, nocturnal cognitive arousal (broadly focused and perinatal-specific), perseverative thinking, depression, infant colic, infant sleep quality, and mother-infant relationship quality. Mixed effects models were conducted to test hypotheses. Results: Prenatal snoring and weak maternal-fetal attachment augured poorer postpartum bonding. Poor infant sleep was associated with increased odds for maternal insomnia and short sleep. Impairments in the mother-to-infant bond were linked to maternal insomnia, nocturnal perinatal-focused rumination, daytime sleepiness, depression, and poor infant sleep. Postnatal insomnia predicted future decreases in mother-infant relationship quality, and nocturnal cognitive hyperarousal partially mediated this association. Conclusion: Both maternal and infant sleep problems were associated with impairments in mother-to-infant bonding, independent of the effects of maternal depression and difficult infant temperament. Perseverative thinking at night, particularly on infant-related concerns, was linked to impaired bonding, rejection and anger, and infant-focused anxiety. Improving maternal and infant sleep, as well as maternal cognitive-emotional regulation, may improve the maternal-to-infant bond. Support (if any): This work was funded by the American Academy of Sleep Medicine (198-FP-18, PI: Kalmbach). Dr. Cheng's effort was supported by the National Heart, Lung, and Blood Institute (K23 HL138166, PI: Cheng).